The Alleviating Effect of Arginine on Ethanol Stress in Wickerhamomyces anomalus - Yinfeng Li; Yujie Wang; Shuangyan Liu; Guilan Jiang; Mingzheng Huang; Xiaozhu Liu (Journal of Fungi)
Yeast cells are passively exposed to ethanol stress during alcoholic fermentation, ultimately impairing cell viability and reducing fermentation efficiency. Arginine, a versatile amino acid, plays a crucial role in regulating cellular responses to various stresses. This study aimed to explore the underlying mechanism by which arginine protects Wickerhamomyces anomalus against ethanol stress. The effects of arginine supplementation (5 mM) under ethanol stress (9% v/v) on cell survival, reactive oxygen species (ROS) production, cellular and mitochondrial membrane integrity, and nitric oxide synthesis were investigated using fluorescent staining methods. Furthermore, differentially expressed genes (DEGs) and metabolites (DEMs) were identified through transcriptomics and metabolomics analyses. The results demonstrated that exogenous arginine enhanced cell survival, reduced ROS levels, maintained cellular and mitochondrial membrane integrity, stimulated nitric oxide production, and modulated gene expression and metabolic pathways involved in pyruvate metabolism, yeast meiosis, fatty acid degradation, glycerophospholipid metabolism, and the biosynthesis of various secondary metabolites. These findings provide intriguing insights into the mechanistic role of arginine in enhancing the tolerance of W. anomalus to ethanol stress, and broaden its application in the fermentation industry for alcoholic beverages.